GAGASAN PEMBAHARUAN PENDIDIKAN ISLAM MUHAMMAD ABDUH (1849-1905) - Cahaya Khaeroni (Universitas Muhammadiyah Metro, 2017)
This paper analyzes the contributions of Shaykh Muhammad ‘Abduh to modernity, and his struggle for change and reform in Egyptian society. Abduh was hailed as the “first leader of modern thought in Egypt”, “the father of the 20th century Muslim thought” and “pioneers of the modernist movement in the Arab world”, whose legacy in the history of Islamic reform was significant, carrying dynamic role in the transformation and reinterpretation of Islam in contemporary thought. His contribution to Islamic modernism was clearly seen in liberalizing the educational system, transforming the Islamic worldview, and integrating western and Islamic ideals and tradition. Keywords: Muhammad Abduh, Islamic modernism, educational reform.